The Effect of Government Internal Auditor's Competency and Professionalism on Audit Quality : Case Study on the Auditor of the DKI Jakarta Financial and Development Supervisory Agency - Shofia Asry (Kusuma Negara Business School, 2021)
Developments in all sectors at this time have quite affected the profession of independent auditors, in this case government auditors. Government auditors are auditors who work in government agencies whose main task is to audit the financial accountability of various organizational units within the government. This auditing is carried out by government auditors, one of which is the Internal Auditor who works at the BPKP Finance and Development Supervisory Agency (BPKP). The purpose of this study was to determine the effect of Competence and Professionalism of Government Internal Auditors on Audit Quality at Representatives of the Financial and Development Supervisory Agency for the Special Capital Region of Jakarta. The results of this study indicate that there is a simultaneous influence of Competence and Professionalism of Government Internal Auditors on Audit Quality at Representatives of the Financial and Development Supervisory Agency for the Special Capital Region of Jakarta. This is indicated by the calculated F value of 11.752 which is greater than the F table of 3.42 and indicated by the sig of 0.000 which is smaller than 0.05. From the results of the calculation of determination (R2) that is equal to 0.763 which means that the Competence and Professionalism of the Government's Internal Auditor simultaneously affect the Quality of Audit at the Representative of the Financial and Development Supervisory Agency for the Special Capital Region of Jakarta by 76.3%.